The weird eusociality of polyembryonic parasites - Whyte, Brian A. (Biology letters (2005), 2021)
Some parasitoid wasps possess soldier castes during their parasitic larval stage, but are often neglected from our evolutionary theories explaining caste systems in animal societies. This is primarily due to the polyembryonic origin of their societies. However, recent discoveries of polyembryonic trematodes (i.e. flatworms) possessing soldier castes require us to reconsider this reasoning. I argue we can benefit from including these polyembryonic parasites in eusocial discussions, for polyembryony and parasitism are taxonomically vast and influence the evolution of social behaviours and caste systems in various circumstances. Despite their polyembryony, their social evolution can be explained by theories of eusociality designed for parent–offspring groups, which are the subjects of most social evolution research. Including polyembryonic parasites in these theories follows the trend of major evolutionary transitions theory expanding social evolution research into all levels of biological organization. In addition, these continued discoveries of caste systems in parasites suggest social evolution may be more relevant to parasitology than currently acknowledged.